Effect of the gibberellic acid , benzyl adenine and exposure period of ultrasound waves on seed germination and seedling growth of mesquite (Prosopis cineraria L.) .: Effect of the gibberellic acid , benzyl adenine and exposure period of ultrasound waves on seed germination and seedling growth of mesquite (Prosopis cineraria L.) . - Shareef, Sabah Gazi; Alkeliby, Chaseb Khazaal Jawad; Alsafar, Iman Mohammad Abbas; Hamzah, Roaa Mahdi (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment was carried out at Collage of Agriculture / University of Kerbala in mid of April 2016 to the March 2017 according to the design of random complete block (RCBD). The purpose of this article is to study the effect of concentration of gibberellic acid (0,150 and 300 mg . L-1), Benzyl adenine acid concentration (0,50 and 100 mg . L-1) and the exposure period to ultrasound waves (0 and 120 min) on seed germination and seedling growth of mesquite (Prosopis cineraria L.). The results showed that the treatment of gibberellic acid (300 mg . L-1) was attained higher significantly value in all studied traits compared to the control treatment. The percentage increment of germination seedlings at this concentration was 41.74 % . Secondly, the treatment of benzyl adenine acid (100 mg. L-1) was effected highly significant in all studied properties except for relative moisture content. While, the ultrasound treatment (120 minutes) gave higher significant value. The values were in ratio of germination, stem diameter and total chlorophyll compare to the control treatment. The percentage increment were 26.01 , 12.91 and 28.94 % respectively. Thirdly, the interaction treatment between concentration of gibberellic acid (300 mg. L-1) and benzyl adenine acid (100 mg. L-1) gave highly values for all the properties which have been studied, compare to control treatment. In addition, the interaction treatments between gibberellic acid (300 mg. L-1) and ultrasound (120 minutes) have been given highly significant values for all properties studied. Excepting plant height and stem diameter compared to control treatment. Finally, the trible interaction results among gibberellic acid (300 mg. L-1) , benzyl adenine acid (100 mg. L-1) and ultrasound (120 minutes) showed high significant values for all the properties studied, excepting relative moisture content for plant leaves compared with control treatment and the value of rate seeds germination gave 73.33 % compared to control treatment 20.00 %.